KEPEMIMPINAN TRANSFORMASIONAL MEMODERASI PENGARUH KOMITMEN ORGANISASIONAL DAN MOTIVASI TERHADAP KINERJA GURU (Studi Pada Guru SMK Negeri Se Sub Rayon 01 Kota Semarang) - Salim, Salim; Suhari, Y (Jurnal Ilmiah Telaah Manajemen, 2017)
This research purpose are to aim and analyze the affect on organizational commitment, affective organizational commitment, continuance organizational commitment, Normative organizational commitment, intrinsic motivation, and idealized influence transformational leadership to teacher teaching performance. Population in this research are 260 teachers of Vocational high school in sub Rayon 01 in Semarang. Sample are 135 respondent chosen by a random sampling method. Data collected methode are questionnaires. Data analyze technique use double regression technique. Result shown that organizational commitmentnot affectingsignificant and possitively teacher teaching performace.Affective organizational commitmentnot affectingsignificant and possitively teacher teaching performace.Continuance organizational commitmentnot affecting significant and possitively teacher teaching performace.Normative organizational commitmentnot affectingsignificant and possitively teacher teaching performace.Intrinsic motivation affecting significant and possitively to teacher teaching performance.Idealized influence transformational leadership moderating significant and possitively the effect of organizational commitment to the teacher teaching performace.Idealized influence transformational leadership is not moderating significant and possitively the effect of affective organizational commitment to the teacher teaching performace.Idealized influence transformational leadership is not moderating significant and possitively the effect of continuance organizational commitment to the teacher teaching performace.Idealized influence transformational leadership is not moderating significant and possitively the effect of normative organizational commitment to the teacher teaching performace.Idealized influence transformational leadership is not moderatingsignificant and possitively the effect of Intrinsic motivation to the teacher teaching performace. Keywords : Organizational commitment, Affective organizational commitment, Continuance organizational commitment, Normative organizational commitment, Intrinsic motivation,Idealized influence transformational leadershipandteacher teaching performance.